Pre-schooler learning system using mobile application - Ramani, Deepa (2012)
The Pre-schooler Learning System using Mobile Application is focusing on earliest exposure c education system which will be alphabets and numbers recognition and application. Instead of hardcor materials and computer as the learning and teaching medium,parents and teachers can use this mobil( learning application to teach their kids and students wherever and whenever they want.The primary us for this system is pre-schooler and the secondary users are the elder people such as parents,teachers,at siblings to guide and teach the primary user.Teachers,parents or guidance can apply this application into their mobile and teach the kids from time to time wherever and whenever.In addition,this systen may help the kids to learn interactively with fun and safe as well.They can also learn at home and not only in school or kindergarten in which through parent's mobile phone with parents'guide.This syster is focusing on the importance of getting the kids attention towards studying by implementing animatior sound from various source,attractive pictures and colours.This system have been developed with the assist of a basic survey which was conducted at Tadika Minda Lestari located at Taman Astana Permai,Jalan Bukit Istana,Bandar Indera Mahkota,Kuantan, Pahang Darul Makmur.In this survey,30 preschoolers,5 teachers and 10 parents participated.The most essential element that have been highlighted in this project is the element of Human Mobile Interaction.Pre-Schooler Learning System using Mobile Application is developed using Aptana Studio 2.0 with HyperText Markup Language (HTML).The most important hardware or device that will be needed for this system is Nokia touchscreen Mobile Phone.The'always on' nature of mobile devices provides access on demand for th kids,maximizing the potential for delivering valuable content at the point of need.